Effect of meteorology on the variability of ozone in the troposphere and lower stratosphere over a tropical station Thumba (8.5°N, 76.9°E). (April 2021) - Satheesh Chandran, P.R.; Sunilkumar, S.V.; Muhsin, M.; Emmanuel, Maria; Ramkumar, Geetha; Nair, Prabha R.
Abstract: Seasonal variability in the vertical distribution of ozone over a tropical station, Thumba (8.5°N, 76.9°E) is investigated using nine-years (2011–2019) of ECC ozonesonde data obtained as part of Tropical Tropopause Dynamics (TTD) campaigns. Ozone exhibits a clear annual variation in the lower troposphere (0–2 km) with winter maximum (49.2 ± 3.6 ppbv) and summer monsoon minimum (21.9 ± 0.7 ppbv). In the middle (2–10 km) and upper (11–17 km) troposphere, ozone is maximum in pre-monsoon and minimum in summer monsoon. Ozone in the lower stratosphere exhibits a clear annual variation with summer monsoon maximum and winter minimum in tandem with the temperature cycle. The relative standard deviation (RSD) of ozone computed at different altitudes exhibits large intra-seasonal variability in the troposphere ( 20–30%) compared to the stratosphere ( 5%) and is significantly high close to the surface and in the tropical tropopause layer (TTL) (≥30%). Maximum RSD is observed during summer monsoon (June–September) in the upper troposphere ( 50%) close to cold point tropopause (CPT). RSD in ozone and temperature profiles show a sharp peak immediately above the CPT in all the seasons, coinciding with the altitude of maximum wind shear. Tropospheric ozone shows an in phase relationship with temperature and is opposite in phase with water vapour. A significant negative correlation is observed between ozone and water vapour in the 2–5 km altitude region. Long-range transport and local convection contribute substantially to the observed variability in tropospheric ozone. The tropospheric column ozone shows a semi-annual variation with maximum contribution to the total columnar ozone during pre-monsoon ( 16%) and minimum during summer monsoon ( 8%). Mid-tropospheric ozone contributes more to the tropospheric column ozone (40–60%) compared to lower and upper tropospheric ozone. Tropospheric column ozone exhibits a similar seasonality as that of its precursors like NO2, CO and CH4 . Highlights: Ozone distributions shows high intraseasonal variability near the CPT. Local convection and long-range transport determine tropospheric ozone variability. Significant contribution to the tropospheric column ozone is from the mid-troposphere.